Palynological analysis of the genus Ctenitis (C. Chr.) C. Chr. (Dryopteridaceae) in the Southern Cone of America - Gorrer, Daniel Alejandro (2022)
The spore morphology and wall ultrastructure of 12 species of Ctenitis from Southern Cone of America were studied using light microscope, scanning and transmission electron microscope. The study was carried out with herbarium material from Argentine and Brazilian institutions. Equatorial diameters, polar diameters and laesura length were measured. The spores are monolete with echinate or folded ornamentation. In the echinate type, the spines are conical, with broad base and attenuate apex. In the rugate type, the folds are inflated, linear, sinuous, subglobose or handle-shape. The perispore surface is scabrate, rugulate, microverrucose or psilate. Stratification and ultrastructure in the species analyzed are very similar. The exospore is smooth and two-layered in section. Simple and branched channels are observed mainly in the outer exospore. The perispore is composed of two layers, the inner one forms the ornamentation and the outer covers all the outer and inner surfaces. Immature spores were found in all samples of C. fenestralis. The characteristics of the studied spores like macro-ornamentation, color and fold length provide relevant information to differentiate some species or groups of species within the genus.